In-hospital predictors of 60-day readmission in COVID-19 patients. (14th October 2021) - Ruge, M; Gill, A; Gomez, J M D; Du Fay De Lavallaz, J; Simmons, J A; Williams, K A; Volgman, A S; Marinescu, K; Rao, A; Suboc, T
Abstract: Introduction: Preventing hospital readmissions can improve a patient's quality of life and decrease healthcare costs. While prior work has focused on pre-existing comorbidities to predict COVID-19 readmissions, the prognostic role of in-hospital data and complications has been less studied. Methods: Data was collected on adult patients diagnosed with COVID-19 and admitted to a multicenter hospital system in Illinois between March and November 2020. Our cohort consisted of COVID-19 hospitalization survivors excluding those discharged to hospice care. Major adverse events (MAEs) were defined as venous thromboembolism (VTE), myocardial injury (troponin greater than upper limit of normal), stroke, new requirement for renal replacement therapy (RRT), life-threatening arrhythmia, or acute heart failure exacerbation. The primary outcome was readmission within 60 days of initial hospitalization. Results: From the 1406 survivors of the index hospitalization, 223 (15.9%) patients were readmitted within 60 days. Those readmitted were older and more likely to have underlying comorbidities including atrial fibrillation, coronary artery disease, and hypertension (Table 1). Length of stay between the readmission and non-readmission groups was trending towards statistical significance (10.52 days vs 8.95 days, p=0.053). Those with one or more MAE during their index hospitalization, when adjusted for age and body mass index, were at an increased risk of readmission (adjusted odds ratio [aOR] 1.90, p<0.01). Readmitted patients were more likely to have VTE during their index hospitalization than those not readmitted (7.2% vs 3.7%, p<0.05). The incidence of new RRT (4.9% vs 2.5%, p=0.083) and myocardial injury (3.6% vs 1.5%, p=0.067) between the groups was also trending towards statistical significance (Table 1). No statistical difference was present between the other individual MAEs; however, this is limited by small sample sizes of certain MAEs. Of the 322 patients with echocardiography during the index admission, 82 (25.5%) were readmitted. In this cohort, left ventricular ejection fraction (LVEF) that was reduced (LVEF <50%) or hyperdynamic (LVEF >65%) was not a statistically significant predictor of readmission (Figure 1). Lastly, discharge disposition was predictive of readmission as those being sent to acute rehab (OR 2.04, p<0.01), long-term acute care (OR 2.58, p<0.01), or skilled nursing facility (OR 2.67, p<0.001) were at higher risk compared to those who were discharged to home (Figure 1). Conclusion: In this cohort, the occurrence of any MAE during index COVID-19 hospitalization, particularly VTE, RRT, and myocardial injury, can be used to predict 60-day readmission. Furthermore, discharge disposition, but not LVEF, demonstrated prognostic value in our cohort. Identifying high risk patients prior to discharge helps health care providers focus resources on patients most likely to be readmitted. FUNDunding Acknowledgement: Type of funding sources: None.